Unpaid Domestic Labour in Pukhtun Households: Invisibility, Recognition, and Political Subjectivity - Hamza Israr; Nayab Bibi (Journal of Feminism and Gender Studies, 2026)
This article examines the invisibility and undervaluation of women’s unpaid domestic labour in Pukhtun households, despite its centrality to family well-being, everyday chores, and wider economic participation. We draw on feminist methodology and political ethnography. The study is based on interviews, time-use diaries, and participant observation in rural Mardan and urban Peshawar. Three themes emerge: the unequal distribution of burden and recognition, where women’s continuous labour is naturalised while men’s intermittent contributions are celebrated; the translation of this invisibility into women’s limited authority in household decision-making; and the intersection of paid domestic work with class and gender hierarchies that reinforce precarity. The analysis shows that time poverty, honour codes, and spatial practices in the home render women’s work indispensable yet politically erased. Small acts of refusal, bargaining, and solidarity reveal constrained but significant political subjectivities. We argue that recognising unpaid domestic labour requires not only legal protections for paid workers and investment in public care infrastructure, but also culturally grounded organising strategies that make invisible labour visible and actionable in Pukhtun contexts.